Scale-Adaptive Simulation on the Reactive Turbulent Flow in a Partial Combustion Lance: Assessment of Thermal Insulators - Law, Woon Phui; Jolius, Gimbun (Elsevier Ltd, 2016)
This paper presents a scale-adaptive simulation (SAS) of a partial combustion lance (PCL) aiming to evaluate the influence of thermal insulation on the performance of syngas combustion. Standard k–ε (SKE) and Reynolds stress model (RSM) were used for comparison. The combustion reaction was modelled using eddy dissipation model (EDM), non-premixed and partially premixed flame models. Discrete ordinates (DO) and spherical harmonics (P-1) were used to calculate the radiative heat transfer. The finding suggests that SAS provides a better prediction for reactive turbulent flow. In the present work, simulation of syngas combustion using non-premixed flame with a DO approach showed the best agreement with experimental data by about 5.3%. Installation of an insulator increases the peak outlet temperature by about 20.4%.